LACANIAN PSYCHOANALYSIS: MA’S DESIRE IN ROOM (2015) - Amelia Syarani (ELT (English Language Teaching Prima Journal), 2026)
This study aims to analyze the representation of Ma’s desire in the film Room (2015) through a Lacanian psychoanalytic perspective. The study is based on Lacan’s concept that desire emerges from a sense of lack and shapes human experience through three main realms: the Real, the Imaginary, and the Symbolic. The film portrays Ma’s psychological struggle as she lives in captivity with her son, Jack, creating a complex dynamic of desire as she attempts to survive and protect her child. A qualitative descriptive method with a Lacanian psychoanalytic approach is applied to examine the film. The study data consists of dialogue, scenes, character expressions, and visual symbols that show the representation of Ma's desires in the film. Data was collected through observation of films, then identified and classified based on three Lacanian realms, namely Real, Imaginary, and Symbolic. The findings of the analysis show that Ma's wishes are reflected in her efforts to build an imaginary world for Jack, maintaining her identity as a protective mother, as well as her desire to get out of the detention room. This desire serves as a psychological force that shapes Ma's actions, survival strategies, and identity development throughout the film's storyline.